Age dependent effects of early intervention in borderline personality disorder in adolescents - Kaess, Michael; Thomson, Madelyn; Lerch, Stefan; Koenig, Julian; Fischer-Waldschmidt, Gloria; Reichl, Corinna; Cavelti, Marialuisa (Psychological medicine, 2024)
Background. Psychological treatments for young people with sub-threshold or full-syndrome borderline personality disorder (BPD) are found to be effective. However, little is known about the age at which adolescents benefit from early intervention. This study investigated whether age affects the effectiveness of early intervention for BPD. - Methods. N = 626 participants (M age = 15 years, 82.7% female) were consecutively recruited from a specialized outpatient service for early intervention in BPD in adolescents aged 12- to 17-years old. DSM-IV BPD criteria were assessed at baseline, one-year (n = 339) and two-year (n = 279) follow-up. - Results. Older adolescents presented with more BPD criteria (χ2 (1) = 58.23, p < 0.001) and showed a steeper decline of BPD criteria over the 2-year follow-up period compared with younger adolescents (χ2 (2) = 13.53, p = 0.001). In an attempt to disentangle effects of early intervention from the natural course of BPD, a parametrized regression model was used. An exponential decrease (b = 0.10, p < 0.001) in BPD criteria was found when starting therapy over the 2-year follow-up. This deviation from the natural course was impacted by age at therapy commencement (b = 0.06, p < 0.001), although significant across all ages: older adolescents showed a clear decrease in BPD criteria, and young adolescents a smaller decrease. - Conclusions. Early intervention appears effective across adolescence, but manifests differently: preventing the normative increase of BPD pathology expected in younger adolescents, and significantly decreasing BPD pathology in older adolescents. The question as to whether developmentally adapted therapeutic interventions could lead to an even increased benefit for younger adolescents, should be explored in future studies.
Gesehen am 19.08.2024